2018
DOI: 10.1136/bmjopen-2017-019730
|View full text |Cite
|
Sign up to set email alerts
|

Association between recreational drug use and sexual practices among people who inject drugs in Southwest China: a cross-sectional study

Abstract: ObjectiveTo describe the differences in sexual practices among individuals with various drug administration patterns.SettingA detoxification centre in Southwest China, a part of the Chinese national sentential surveillance network for hepatitis C virus (HCV), HIV and syphilis infections, was recruited.ParticipantsA total of 610 newly enrolled injection drug users (IDUs) from detoxification centre were included during 2015.Primary and secondary outcome measuresSelf-reported sexual activities, drug-related pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The ndings indicate that substantially higher proportion of the interviewed PWID had multiple sex partners (64.9% had ≥ 3 sexual partners) compared to other studies conducted in different countries where this indicator varied between 14-47% [30,31,32,33,34]. We also found a high prevalence of unprotected last sexual intercourse with any type of sexual partner among PWID and this nding is consistent with other studies [35,36,37,38].…”
Section: Discussionsupporting
confidence: 90%
“…The ndings indicate that substantially higher proportion of the interviewed PWID had multiple sex partners (64.9% had ≥ 3 sexual partners) compared to other studies conducted in different countries where this indicator varied between 14-47% [30,31,32,33,34]. We also found a high prevalence of unprotected last sexual intercourse with any type of sexual partner among PWID and this nding is consistent with other studies [35,36,37,38].…”
Section: Discussionsupporting
confidence: 90%
“…First, condom use is increasing among people who use heroin and SD, so it has impacts on reducing sexual transmission. Second, as our model considered the transfer trend within three subgroups, long-term SD use is likely to be polydrug use and moving to the polydrug group,6 while long-term heroin users will reduce sexual desire due to the heroin effects,8 so there may be a balance impact on syphilis epidemics during the study period. Thus, it could be efficient to implement interventions on reducing sexual transmission in the SD group to benefit all the people who use drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Also, our previous model has estimated the number of people who use drugs will increase, and there is a changing trend of drug use that more monodrug use becomes polydrug use,6 and it will likely have impacts on the transmission modes of these infections as well. SDs have different effects from heroin; cumulating evidence has indicated that the common SDs are shown to be associated with higher risk sexual behaviours (eg, multiple sexual partners and condomless sex) 7 8. Furthermore, in order to increase pleasure, heroin is often ingested concurrently with an SD (eg, cocaine or methamphetamine), and it is called polydrug use 9.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The infusion of fentanyl into the Indian drug supply will likely produce similar results. Interestingly, Chinese PWID who used SD exclusively engaged in more frequent and risky sexual activity relative to polydrug or heroin-only users (78). If IMF increases sexual activity, increased use in India may contribute to the rise of HIV, HCV, and other sexually transmitted diseases.…”
Section: The Public Health Consequences Of Increased Production Of Im...mentioning
confidence: 99%